The Prevalence of Abnormal Pap Smears in females Referred to Health Centers Affiliated to Medical Sciences During the Years 2012 to 2016 - Zahra Massomi; Somayeh Khani; Maryam Gharosian; Maryam Farhadian; Arezo Shayan (Journal of Education and Community Health)
Background and Objectives: Cervical cancer is one of the most important female reproductive system diseases. The aim of this study was to estimate the prevalence of abnormal Pap smears of pregnant females in public health centers and hospitals of Hamadan.